Effect of HSPA8 gene on the proliferation, apoptosis and immune function of HD11 cells. (May 2023) - Tian, Huihui; Ding, Mengxia; Guo, Yujie; Zhu, Zhaoyan; Yu, Yange; Tian, Yadong; Li, Kui; Sun, Guirong; Jiang, Ruirui; Han, Ruili; Yan, Fengbin; Kang, Xiangtao
Abstract: HSPA8 (Heat shock 70 kDa protein 8) is a molecular chaperone involved in a variety of cellular processes. This gene may affect the proliferation, apoptosis and immune function of chicken macrophages, but the specific mechanism remains unclear. The purpose of this study was to explore the effect of the HSPA8 gene on the proliferation, apoptosis and immune function of chicken macrophages. In this study, a chicken HSPA8 overexpression plasmid, interference fragment and corresponding controls were transfected into HD11 cells, and then the expression of the HSPA8 gene, cell proliferation, cell cycle, apoptosis rate and immune function of each group were detected. The results showed that transfection of the HSPA8 overexpression plasmid significantly upregulated the level of HSPA8 expression in HD11 cells compared with the control; significantly promoted the proliferation of HD11 cells and the expression of PCNA, CCND1 and CCNB3 ; decreased the number of cells in the G1 phase and increased the number of cells in the S phase; decreased the rate of apoptosis and upregulated the expression of Bcl-2 ; and promoted the expression of the LPS-induced cytokines IL-1β, IL-6 and TNF-α . Transfection of the HSPA8 interference fragment significantly downregulated the level of HSPA8 expression in HD11 cells; significantly inhibited the proliferation of HD11 cells and the expression of PCNA, CCND1 and CDK1; increased the number of cells in the G1 phase and decreased the number of cells in the S phase; increased the rate of apoptosis, downregulated the expression of Bcl-2 and upregulated the expression levels of Fas and FasL ; and inhibited the expression of the LPS-induced cytokines IL-1β and NF-κB . The results suggested that HSPA8 promotes the proliferation of and inhibits the apoptosis of HD11 cells and has a proinflammatory effect. Highlights: HSPA8 can promote the proliferation of HD11 cells. HSPA8 can inhibit the apoptosis of HD11 cells. HSPA8 is involved in regulating the immune response of HD11 cells. HSPA8 promotes inflammation by promoting the expression of LPS-induced inflammatory factors.